CFD comparison of friction and pressure drag between road and time trial helmets for wheelchair racing - Forte, Pedro (2016)
Computer Fluid Dynamics (CFD) has been used by sports scientists aiming to improve the athlete’s performance in sprinting events. In wheelchair sprinting velocity can reach 7m/s. Sports garment such helmets may reduce aerodynamic drag by 10%. The aim of this study was to compare the friction and pressure drag between a road and time trial helmet.